Blind channel equalization in GI-less OFDM systems using property restoral - Alayyan, F.; Shubair, R.; Zoubir, A.; Leung, Yee-Hong (2010)
We introduce a new low complexity equalizer for Orthogonal Frequency Division Multiplexing systems with virtual carriers. The proposed equalizer utilizes the existing redundancy in the frequency domain to completely eliminate the effects of inter-symbol-interference. We prove the usage of frequency domain redundancy is effective to extract the transmitted signals. © 2009 IEEE.